An external dosimetry audit programme to credential static and rotational IMRT delivery for clinical trials quality assurance. (March 2017) - Eaton, David J.; Tyler, Justine; Backshall, Alex; Bernstein, David; Carver, Antony; Gasnier, Anne; Henderson, Julia; Lee, Jonathan; Patel, Rushil; Tsang, Yatman; Yang, Huiqi; Zotova, Rada; et al.
Highlights: External dosimetry audit programme implemented for clinical trials using IMRT. Good agreement between measured and planned dose distributions. Outliers given feedback to improve clinical practice. Tolerance table derived to aid future credentialing. Abstract: Purpose: External dosimetry audits give confidence in the safe and accurate delivery of radiotherapy. The RTTQA group have performed an on-site audit programme for trial recruiting centres, who have recently implemented static or rotational IMRT, and those with major changes to planning or delivery systems. Methods: Measurements of reference beam output were performed by the host centre, and by the auditor using independent equipment. Verification of clinical plans was performed using the ArcCheck helical diode array. Results: A total of 54 measurement sessions were performed between May 2014 and June 2016 at 28 UK institutions, reflecting the different combinations of planning and delivery systems used at each institution. Average ratio of measured output between auditor and host was 1.002 ± 0.006. Average point dose agreement for clinical plans was −0.3 ± 1.8%. Average (and 95% lower confidence intervals) of gamma pass rates at 2%/2 mm, 3%/2 mm and 3%/3 mm respectively were: 92% (80%), 96% (90%) and 98% (94%). Moderately significant differences were seen between fixed gantry angle and rotational IMRT, and between combination of planning systems and linac manufacturer, but not between anatomical treatment site or beam energy. Conclusion: An external audit programme has been implemented for universal and efficient credentialing of IMRT treatments in clinical trials. Good agreement was found between measured and expected doses, with few outliers, leading to a simple table of optimal and mandatory tolerances for approval of dosimetry audit results. Feedback was given to some centres leading to improved clinical practice.